Evaluasi User Experience Game Raft menggunakan Metode Game Experience Questionnaire (GEQ) - Darmadani Kyat Madana; Eriq Muhammad Adams Jonemaro; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Raft is a survival game developed by Redbeet Interactive and Axolot Games while still in the Early Access stage. Therefore, the game requires an evaluation of the user experience before reaching final stage of development. The method used in this study is the Game Experience Questionnaire, a questionnaire-based instrument that aims to measure user experience in playing games. The questionnaire has 3 modules. The first module is the Core Module with an average value result of 3 on dimensions such as Competence (M = 2.99, SD = 1.05175), Immersion (M = 3, SD = 1.03061), and Positive Effect (M = 3.1, SD = 1.019152) while the lowest value results are on dimensions such as Negative Effect (M = 0.9875, SD = 1.293767) and Tension (M = 0.817, SD = 1.38392). The second module is the Social Presence Module. However, it is not used for this research because it is preferred for games which require many players. The respondents will only be playing play the game in singleplayer for the purposes of this study. The third module is the Post-Game Module with the highest score on the Positive Experience dimension (M = 2.6833, SD = 1.07958) while the lowest score on the Negative Experience dimension (M = 0.60, SD = 1.00536). The results of the Raft game user experience are of good value. However, there are some issues that arise and do not affect the gameplay completely because they are minor.